Investigation of different load transmission concepts for coreless filament wound structures. (1st January 2023) - Mindermann, Pascal; Kaiser, Patrick; Müller, Lena; Fischer, Lisa; Gebhardt, Philipp; Hindenlang, Ulrich; Gresser, Götz T.
Highlights: Several load transmission concepts in tension and compression were investigated. Secondary winding pins drastically increase the failure load in tension. The mechanical impact of the consolidation for coreless filament winding was quantified. Abstract: Sparse composite frameworks can be produced integrally using coreless filament winding, resulting in components with high mass-specific performance that are mainly used in aerospace, automotive, and construction applications. The fiber orientation can be individually set to match the load direction, allowing high load capacities with minimized material usage. However, failure mainly occurs near the load transmission regions substantially before the load-carrying capacity of the actual straight fiber strand element is exhausted. This paper presents an experimental investigation on several concepts for arranging the fiber composite around the load transmitting pin in coreless filament winding. The samples' mechanical performances and failure behaviors in tension and compression were compared, based on force–displacement data, to improve the design of the transition element. The mechanical performance was improved by introducing secondary winding pins, additional wrapping of the fiber strand, or adding smoothening fiber guiding elements. Additionally, the impact of the consolidation on the coreless filament wound elements was quantified to negatively impact tensile load absorption.